Cell-type specific responses to interleukin-1 control microbial invasion and tumor elicited inflammation in colorectal cancer - Dmitrieva-Posocco, Oxana (Immunity, 2019)
Chronic inflammation drives the progression of colorectal cancer (CRC). Increased expression of interleukin (IL)-17A is associated with poor prognosis, and IL-17A blockade curbs tumor progression in preclinical models of CRC. Here we examined the impact of IL-1 signaling, a key regulator of the IL-17 pathway, in different cells types within the CRC microenvironment. Genetic deletion of the IL-1 receptor (IL-1R1) in epithelial cells alleviated tumorigenesis in the APC model of CRC, demonstrating a cell-autonomous role for IL-1 signaling in early tumor seed outgrowth. T cell specific ablation of IL-1R decreased tumor-elicited inflammation dependent on IL-17 and IL-22, thereby reducing CRC progression. The pro-tumorigenic roles of IL-1 were counteracted by its effects on myeloid cells, particularly neutrophils, where IL-1R1 ablation resulted in bacterial invasion into tumors, heightened inflammation and aggressive CRC progression. Thus, IL-1 signaling elicits cell type-specific responses which, in aggregate, set the inflammatory tone of the tumor microenvironment and determine the propensity for disease progression.